The Little Book on Permafrost - Yoshikawa, Kenji (Arctic Portal / Page 21, 2013)
This e-learning material was created within the “PAGE21 – Permafrost in the Arctic and its Global Effects in the 21st Century“ project. The project is an EU Seventh Framework Programme funded large scale integrating collaborative project, aiming to understand the interactions between the global climate system and the frozen ground. The multidisciplinary nature of the science and the wide range of countries covered in the PAGE21 project combine to provide a wealth of opportunities for disseminating information. One of the tasks within the project was to create materials for education and training and that way ensure that the vast amount of knowledge entailed in the project consortium will be distributed to the widest possible audience for the benefit of community as a whole. This e-learning material “Little book on Permafrost” was created by the PAGE21 participant Arctic Portal in Iceland with the support of the PAGE21 project office as well as the project coordination team at Alfred Wegener Institute, Potsdam, Germany.